OPTIMIZING CRITICAL THINKING SKILL THROUGH PEER EDITING TECHNIQUE IN TEACHING WRITING - Nur Muthmainnah (STKIP Siliwangi, 2019)
The objective of the research was to know the description of how critical thinking skill can be optimized in teaching writing using peer editing technique. Critical thinking skill should be strengthened in writing class to elicit the writing class problem. Applying peer teaching technique was assumed can optimize the critical thinking skill in writing class. This research used descriptive qualitative method. It was conducted to the students of English Education Department students in paragraph based writing class. The writer took one of six classes as the sample of the research. The researcher used observation and documentation to know the description of the class situation. The data which was collected are in form documentation, observation and interview result and students writing and peer editing form which is analyzed descriptively. After the research conducted it can be drawn a conclusion that teaching writing using peer editing can optimize the students’ critical thinking skill. It was proven with the minimal error that was produced in the next writing produced and the increasing score of students’ writing. The mean score in the pre-research was 68.62, after the treatment conducted the mean score increased up to 72.90.